Studi Tentang Bangkitan Lalu Lintas Di KawasanPerumahan Terhadap Jalan Raya Hankam Bekasi - Mardanih Mardanih; Zefri Zefri; Soekmana Soma (Jurnal Kajian Wilayah dan Kota, 2022)
The purpose of this research is to study and calculate the volume of traffic generated byhousing activitieson Jalan Raya Hankam, Estimating the addition of traffic volume with the growth of movement fromhousing on Jalan Raya Hankam. Identify the decline in the level of road service, provide alternativesolutions to problems that arise as a result of additional traffic volumes on Jalan Raya Hankam, to analyzethe effect of transportation problems on road performance, to analyze the effect of environmental pollutionon road performance. Data collection techniques using field surveys and direct communication throughinterviews. The analysis of traffic generation in the residential area of Jalan Raya Hankam requires dataon the socio-economic characteristics and travel movement patterns of residential residents. To obtainthese data, it is necessary to conduct a field survey method, as described below, which includes trafficcounting to determine the amount of trip generation at the entrance and exit of housing as well as theamount of trip generation and the home interview method. The theoretical model in analyzing thehypothesized relationships was developed and tested with the help of multiple regression analysistechnique procedures through the SPSS program. The results of this study show that there is an influenceof transportation problems, environmental pollution, energy consumption, land and aesthetics, trafficcongestion, and public policy on road performance